Execution of Fiduciary Guarantees Post 2019 MK (Constitutional Court) Ruling - Zikry, Bagas Bi; Harahap, Mhd. Yadi; Saragih, Nabila Fadiyah Shafa; Harahap, Kholid; Desky, Saddam Pardamean; Wahyudi, Wahyudi (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Fiduciary guarantee is a language that is often used in Indonesian and also in Law No. 42 of 1999. Collateral is an asset owned by a borrower to be used as collateral or deposit for the loan he receives which is handed over to the lender. The transfer of an ownership right to an object with a sense of mutual trust on mutually agreed terms, namely to an object whose ownership rights are transferred remains under the control of the original owner of the object. Historically, fiduciary institutions have been established since Roman times. As history progressed, Roman law also developed until the emergence of pawning and mortgage institutions. This causes the role of fiduciary institutions as debt collateral to begin to diminish and their existence has also disappeared. This happened after the classical era under the leadership of Justianus.